Dell Inc. : Will The Powerhouse PC Maker Turnaround? - Hong , She San (Agnes) (2007)
This project paper focuses on a case study on Dell. Some of the key subjects includes its major achievements in the past and the present; the overview of the industry - socio,economic,, marketing, political, legal and technological factors that encourage and affect growth and development industry which the company belongs. the challenges of competitors and ways to overcome them; secrets of Dell\'s success - customer experience and employee experience; the power of Direct Model, the partnership strategy, outsourcing strategy, and recent challenges of the company and their solutions. Part two, includesa case analysis of Dell Inc.